Projecting dependency syntax labels from English into Vietnamese in English-Vietnamese bilingual corpus. (26th June 2020) - Tran, Phuoc; Duong, Van-Deo; Dinh, Dien; Vo, Bay; Nguyen, Huu; Nguyen, Long H.B.
In natural language processing, the corpora play an important role, particularly labelled corpora, such as labelled part-of-speech corpora, labelled component syntax corpora, and labelled dependency syntax corpora. These labelled corpora are used for corpus-based research and give higher quality results than the non-labelled. In this paper, we have conducted a Vietnamese dependency label tagger based on English-Vietnamese bilingual corpus, in which English was tagged with dependency labels. The experimental results show that our method produces a high tagging result with LAS measurement of 73.5% and UAS measurement of 81.7%.